Socio-environmental tragedy: Land subsidence in five neighborhoods of Maceió/AL (PerCursos, 2025)
Since 2018, Maceió, the capital of Alagoas State in Brazil, has experienced land subsidence in five neighborhoods, a phenomenon caused by rock salt mining conducted by the petrochemical company Braskem. Thousands of people and homes have been directly affected, resulting in forced displacement to other locations. The impacts of this process are evident both in the lives of residents and in the socio-spatial reconfiguration of the city, causing tangible and intangible losses of incalculable proportions. Given this scenario, this article aims to analyze the process of land subsidence in Maceió in light of David Harvey’s theory of accumulation by dispossession. It is based on a literature and documentary review, as well as on data regarding the compensation proposals presented, accepted, and paid by Braskem to the victims of the tragedy. This analysis finds that the expulsion of thousands of people from their homes and the appropriation of part of the territory of Maceió by Braskem — at very low cost and with the consent of the State — constitute evidence of violent processes of accumulation by dispossession, in which the interests of capital prevail over the rights and well-being of the affected population.
Keywords: accumulation by dispossession; rock salt mining; Braskem’s crime